Eco-Cultural Economic Education: Community Assistance in Upakara Plant at the Taman Bumi Banten: Eco–Cultural Economic-Education: Pendampingan Penanaman Tanaman Upakara di Kawasan Taman Bumi Banten - Ni Putu Diah Untari Ningsih; I Ketut Dani Budiantara; Ayu Widha Erlia (Institut Riset dan Publikasi Indonesia, 2026)
The purpose of this activity was to develop the Taman Bumi Banten area as a platform for Eco–Cultural Economic-Education for the Hindu community through the cultivation of upakara plants. The primary challenges faced by the community partner included: (1) limited supply of upakara materials in Telaga Tawang Village, (2) community dependence on upakara materials sourced from outside Bali, and (3) insufficient knowledge regarding cultivation techniques and the economic potential of upakara plants. A participatory approach was employed, comprising sequential stages of preliminary survey, socialization, training, planting assistance, and evaluation incorporating pre-test and post-test instruments to measure improvements in participants' understanding. The activity was conducted at Taman Bumi Banten, Telaga Tawang Village, Sidemen District, Karangasem Regency, involving approximately 50 participants drawn from lecturers, administrative staff, students, the Seka Truna Truni (STT) youth organization, and local community members. The cultivated upakara plants encompassed various coconut varieties (mulung, gading, gadang, sudamala, and bulan coconut), fruit-bearing species (starfruit, mangosteen, rambutan, and durian), and ornamental flowering plants (jepun and cempaka), totaling 1,011 plants. Pre-test and post-test results demonstrated a mean improvement of 35% in participants' comprehension scores, rising from an average of 58 on the pre-test to 78 on the post-test (on a 100-point scale). Furthermore, the program facilitated the establishment of sustainable cultivation practices and contributed to the development of Taman Bumi Banten as a commodity center for upakara materials and an educational and cultural hub for the Hindu community in Karangasem. These findings demonstrate that assistance-based cultivation of upakara plants is effective in promoting sustainable economic education grounded in cultural and environmental values.